Analisis Kemampuan Kognitif dan Keterampilan Proses Sains Peserta Didik SMA Pada Materi Biodiversitas di Pedesaan dan Perkotaan Aceh - Sulaiman, Nanda Fahira; Syarifuddin, Syarifuddin; Manurung, Binari (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Cognitive abilities and science process skills are important in learning Biology. Biology learning is related to nature so that the region can be a source of learning. Rural and urban areas have different natural conditions, so it is necessary to analyze the cognitive and science process skills of high school students. The purpose of this study was to determine the cognitive abilities and science process skills of high school students in rural and urban areas of Aceh Province. This study is a quantitative descriptive research. The sample in this study was one class from each high school grade X which was determined by purposive sampling technique. The research instruments consisted of cognitive ability tests and science process skills tests. Data analysis was carried out using descriptive statistics and inferential statistics. The results showed that there were differences in cognitive abilities and science process skills of high school students in rural and urban Aceh. The use of technology as a learning medium can help students in accessing sources of biodiversity information outside their environment.